POTENSI MIKROEMULSI β-KAROTEN DALAM MENGHAMBAT FOTOOKSIDASI VITAMIN C SISTEM AQUEOUS [The Potential Inhibition of Β-Carotene Microemulsion on Vitamin C Photooxidation in Aqueous Systems] - Setyaningrum - Ariviani; Sri - Rahardjo; Pudji - Hastuti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
Photooxidation in food system causes nutritional losses and produces undesirable flavor, toxic and color compounds, which make foods unacceptable to consumers. The objective of this research was to determine β–carotene microemulsion inhibitory effect on vitamin C photooxidation in aqueous food model. Into aqueous food models containing vitamin C (450 ppm for model 1; 300 ppm for model 2) 2% microemulsion or β–carotene microemulsion and erythrosine as photosensitizer, were added. The final β–carotene content in aqueous food model was equal to 0.6 or 12 ppm. The result indicated that microemulsion have ability to inhibit vitamin C photodegradation under light but did not show the ability under dark condition. The inhibitory effectiveness of both 6 and 12 ppm β-carotene microemulsion on vitamin C photodegradation were insignificant. The 6 ppm β-carotene microemulsion was proven to effectively inhibit vitamin C photooxidation in aqueous food model better than that of empty microemulsion or free β-carotene. The vitamin C photodegradation rate on model system 1 and 2 were 9.5 ± 2.48 and 6.4 ± 1.58 mg.L-1. hour-1 (β-carotene microemulsion); -14.8 ± 1.69 and -9.5 ± 1.23 mg.L-1. hour -1 (empty microemulsion); -16.0 ± 1.64 and -10.3 ± 0.46 mg.L-1. hour -1 (freeβ-carotene), respectively.